Level of Knowledge and Motivation of Health Workers in the Implementation of EMR at Primary Care - Golo, Zefan Adiputra; Cahyati, Widya Hary; Irmawati, Irmawati (Universitas Negeri Semarang, 2025)
In Indonesia, healthcare facilities have been mandated to adopt Electronic Medical Records (EMR) by 2023. The possession of knowledge and motivation by health workers was identified as a pivotal factor in the successful implementation of EMRs. The aim of this study is to identify the level of knowledge and motivation of health workers with regard to the implementation of EMRs. This is a descriptive and quantitative study that used a cross-sectional study approach. The respondents comprised 39 health workers at Puskesmas Demak II who were administered a questionnaire to ascertain their level of knowledge and motivation regarding EMR implementation. The findings indicated that health workers at Puskesmas Demak II exhibited a commendable level of knowledge (74.4%) regarding EMR, yet their motivation to implement it was found to be suboptimal (51.3%). The Health Office has conducted socialisation of EMR implementation, but Puskesmas are not yet fully prepared in terms of human resources, information system management, budget, internet network infrastructure, and technology. It is the responsibility of the government to ensure the provision of adequate training and technical assistance.